Membaca Ulang Ahmad Hassan: Dialektika Ideologi, Bahasa, dan Toleransi dalam Tafsir Al-Furqan - Aty Munshihah; Zidan Fathoni Fata; Khoerul Anwar (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2025)
This study re-examines Ahmad Hassan’s Tafsir al-Furqan in order to address the recurrent accusations of intolerance leveled against its author. Employing a qualitative design and content-analysis techniques, all verses concerning Muslim–non-Muslim relations in the 1988 edition are isolated as units of analysis and coded according to thematic categories (freedom of belief, autonomy of worship, dialogical ethics) and linguistic features (negation patterns, parenthetical insertions, lexical restrictions). The findings reveal a close dialectic between Hassan’s puritan ideology and his adherence to Qurʾānic linguistic discipline. The three pillars of tolerance—freedom of worship, prohibition of coercing faith, and prohibition of insulting other religious symbols—emerge as direct implications of the Qurʾānic wording, whereas the terms kufr and ṭāghūt are deliberately narrowed to underscore the superiority of Islamic law. Through this model of “conditional tolerance,” Hassan affirms the existential rights of non-Muslims without relativizing Islam’s truth claims. The study thus revises the prevailing “anti-plural puritan” stereotype in the literature and offers a new analytical framework for Indonesian tafsir studies that integrates ideology, language, and social context.